PERBANDINGAN PROFIL LIPID PADA SERUM DARAH PENDERITA HIPERTENSI DAN NORMOTENSI - Widyamurti, Pratiwi; rusdi, Rusdi; Rahayu, Sri (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Increased blood pressure more than 140/90 mmHg taken from three measurement in 24 hours can be diagnosed as hypertension. Abnormality of lipid values condition was found at many hypertensive. Based on this reason examination of lipid profile in hypertensive and normotensive should be done. The aim of this research was to measure and compare lipid profile on blood serum in hypertensive and normotensive. Lipid profile was measured by Konelab 20XT clinical chemistry analyzer. Ex Post Facto used as method and Cross-sectional used as design. A total of 50 blood samples collected from Hypertensive (N1=25) and normotensive (N2=25) from June to August 2014. SPSS 16.0 was used to analyze the data, T-test was used to compare value of LDL cholesterol, HDL cholesterol and total cholesterol while U Mann-Whitney test was used to compare value of triglyceride. The result of this research showed that the mean value of triglyceride was 146.56 mg/dL in hypertensive and 143.92 mg/dL in normotensive (p=0.11). The mean value of LDL cholesterol was 129.80 mg/dL in hypertensive and 136.72 mg/dL in normotensive (p=0.62). The mean value of HDL cholesterol was 38.80 mg/dL in hypertensive and 45.04 mg/dL in normotensive (p=0.1). The mean value of total cholesterol was 201.04 mg/dL in hypertensive and 221.88 mg/dL in normotensive (p=0.25). In conclusion, there was no different of lipid profile on blood serum in hypertensive and normotensive. Keywords: hypertension, lipid profile, normotensive